Estimating seed demand in the presence of market frictions: evidence from an auction experiment in Nigeria - Wossen, T.; Spielman, David J.; Alene, A.; Abdoulaye, T. (Elsevier, 2024)
This paper measures the effect of seed quality misperceptions on bidding behavior and demand for high-quality seed using an information-provision experiment within an incentive-compatible Vickery Second Price (SPA) auction mechanism that mimics seed purchasing decisions in the presence of seed market frictions. We find that most individuals are prone to quality misperception and revise their bids upwards (downwards) in response to positive (negative) quality signals. In addition, by exploiting random variation in the timing of cash grants, we show that imperfect information influences farmer seed valuation, even in the presence of potentially binding liquidity constraints. We also demonstrate that the provision of quality information does not fully resolve quality misperceptions. We then show that unresolved or persistent misperception is severe enough to distort bidding behavior, and ignoring it could lead to biased willingness-to-pay estimates. Our findings have important implications both for improving inference related to the identification and estimation of willingness to pay for quality seed in the presence of market frictions, and for the design of seed sector polices in developing countries.